Suaeda glauca and Suaeda salsa Employ Different Adaptive Strategies to Cope with Saline–Alkali Environments - Xiaoqian Song; Nan Yang; Yuhang Su; Xueyan Lu; Jia Liu; Yang Liu; Zhonghua Zhang; Zhonghua Tang (Agronomy, 2022)
(1) Background: soil salinization has become a global problem that restricts agricultural production; thus, there is a need to explore the special survival strategies of halophytes in saline–alkali environments. (2) Methods: this study conducted a comparative analysis of the differences in metabolites and mineral elements between two indicator plants (Suaeda glauca and Suaeda salsa) in the study area. (3) Results: S. salsa leaves accumulated more total nitrogen (TN), total organic carbon (TOC), calcium (Ca), sodium (Na) and manganese (Mn). The Na/K analysis showed that S. salsa was more tolerant of saline–alkali environments than S. glauca. Metabolite analysis revealed a significant increase in added sugars in S. salsa compared with S. glauca and a significant accumulation of most organic acids associated with the TCA cycle, which suggests an enhancement in the flow of carbon from glycolysis to the TCA cycle. In addition, the content of phenolic substances, such as phenylpropane compounds and flavonols, also changed in saline–alkali environments, which may have promoted the metabolism of organic acids. (4) Conclusions: during the process of plant adaptation to salinity, the central metabolism of S. glauca was nitrogen metabolism, while that of S. salsa was organic acid metabolism.